Bimtek Job Description: Basic Understanding And Methodology Of Preparation - Faozen, Faozen; Siswanto, Edhi; Soeharno, Ageng (Universitas Muhammadiyah Jember, 2023)
The Sidomulyo Tourism Village Development Program aims to overcome various problems related to the preparation of job descriptions in it. Sidomulyo Tourism Village, like many other tourism destinations, faces challenges that need to be overcome so that its operations run more smoothly. One of the main problems faced is the vagueness in the job description which can lead to misunderstandings between workers and managers of Sidomulyo Tourism Village about duties and responsibilities. Sometimes, hired workers do not have qualifications according to the job description, which negatively affects worker performance and satisfaction. Another challenge is crafting job descriptions for unique positions such as tour guides or event organizers who have specific duties. Changes in tourism trends or the local environment can also affect workers' duties. Limited resources for training are an obstacle in improving workers' understanding of their work. Understanding local culture is also important in the tourism industry. To solve this problem, the program offers a solution. Clarification of job descriptions through discussion with workers to identify vagueness. Evaluate the qualifications of workers to ensure conformity with job requirements. Implementation of training programs, workshops, or field trips. Evaluate the impact of training to measure improvements in worker understanding and performance. Adjustment of job descriptions according to the results of evaluations and changes in the industry or environment. Flexibility in dealing with changing tourism trends and the local environment. The aim of the program is for participants to have a better understanding of their duties, history, culture, and local values. This will help them become better ambassadors for Sidomulyo Tourism Village, improve their performance, and contribute to the development of the tourism industry in the village as well as the preservation of the local environment. This program also produces accredited national articles and journals as documentation of the results of their service to the community